Pengaruh Promosi, Shopping Experience Dan Trust Store Terhadap Loyalitas Customer Wilis Vapestore - Mukminin, Abi Amiril; Widarko, Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Competition in the vape industry in Malang is getting tighter with the emergence of many new vape stores offering similar products at competitive prices. The purpose of this study is to analyze and determine the effect of Promotion, Shopping Experience, and Trust Store simultaneously on customer loyalty in Wilis VapeStore customers. This research approach is Quantitative. The population of this study is Customers at Wilis VapeStore who make purchases at least 2 times or more. In this study, the number of samples was determined using the Slovin formula and obtained 75 students. Data were analyzed by multiple linear regression with the help of SPSS 25. The results of the study indicate that there is a simultaneous and partial influence of the variables Promotion, Shopping Experience, and Trust Store on Customer Loyalty. Keywords: Customer Loyalty, Promotion, Shopping Experience, Trust Store.